PERAN GURU AGAMA ISLAM DALAM MENANAMKAN ETIKA PENGGUNAAN WHATSAPP PADA SISWA - ., suntono; Fatmawati, Bella; Mahista, Mia; Naufal Abdi, Mohammad (Jurnal Murid, 2024)
The role of the teacher in instilling the ethics of using WhatsApp to students in this case the teacher plays an important role in guiding and directing teachers of Islamic religious education is as a teacher, guide and role model for students in understanding Islamic teachings, living Islamic values, and applying Islamic teachings in life in the era of globalization and technological advances, as currently the development of the media is very rapid, including WhatsApp media which has become a very popular communication tool and is much needed by people.The aims of this study were: (1) to find out the role of Islamic religious teachers in applying the ethics of using whatsapp to students at MTs Sunan Ampel Kebet Lamongan (2) to find out the supporting and inhibiting factors of teachers in applying the ethics of using whatsapp to students at MTs Sunan Ampel Kebet Lamongan. In this study, a descriptive qualitative research method was used. Data collection was carried out by means of observation, interviews and documentation. And data analysis is done by data reduction, data presentation and data verification (conclusion).Based on the results of the study, it was found that the role of Islamic religious teachers in instilling the ethics of using whatsapp media to students at MTs Sunan Ampel Kebet Lamongan, there are several factors. The main function of the teacher includes three things (1) the teacher's role is to convey knowledge and guide and direct their students. (2) The teacher is also responsible in the form of good moral character in his students because character is the main foundation for strengthening students' self. So as not to fall into bad behavior. then there are supporting factors (1) awareness of the teacher's personal ethics (2) guidance and direction from the teacher. (3) involvement of parents in guiding children, conversely the inhibiting factors are (1) lack of understanding of the material, (2) limited time and material, (3) lack of parental guidance and supervision and environmental background.